ANALGESIC, ANTI-INFLAMMATORY AND ANTI-CONVULSANT ACTIVITIES OF STEM BARKEXTRACT OF ERYTHROPHLEUMIVORENSE(A CHEV) IN RATS AND MICE (2014)
Erythrophleumivorense isused in traditional medicine for the treatment of convulsion, swellings, body pain and as emetic agents. There is a dearth of scientific information in support of the traditional claims. This study was therefore designed to investigate the analgesic, anti-inflammatory and anticonvulsant properties of the methanol extract and fractions ofErythrophleumivorense. Fresh Stem bark of E. ivorense was air dried,ground to powdery form and was extracted using 75% methanol. Crude Methanol Extract (CME, 50g) was fractionated, using ethyl acetate, dichloromethane and n-hexane to yield Ethyl Acetate Fraction (EAF), Dichloromethane Fraction (DCF), and n-Hexane Fraction (HF). Four hundred and eighty male Swiss albino mice (20-25 g) were divided into six experimental groups of twenty animals each for CME and the three fractions. Animals in each group were randomly divided into four treatment groups. Group 1 received 2% DMSO (10mL/kg) (control) while CME or fractions (5, 10, 20 mg/kg) was given to groups 2-4intraperitoneally. Animals were pretreated thirty minutes before injection of acetic acid, formalin or placed in hot plate and picrotoxin, leptazol, strychnine for evaluation of analgesic and anticonvulsant activities respectively. Twenty male Wistar rats (180-200 g) were used for anti-inflammatory study and were randomly divided into four treatment groups. Group 1 received 2% DMSO (10mL/kg) while CME or fraction (5, 10, 20 mg/kg) was given to groups 2-4. All animals were pretreated intraperitoneally thirty minutes before induction of acute inflammation with subplantal injection of carrageenan (0.1ml).Thereafter, the anti-inflammatory activity was evaluated by measuring the oedema size of the right hind paw using cotton thread method.Data were analyzed using descriptive statistic and ANOVA at p=0.05. The CME (20mg/kg), EAF (20mg/kg)and DCF (20mg/kg)caused significant reductionin the number of writhes of acetic acid-induced writhing (3.8±0.4, 3.6±0.2 and 11.9±0.4 respectively) compared with control (37.7±2.6). In hot plate test, CME (7.0±0.5) and EAF (6.6±0.4) significantly prolonged the reaction time (seconds) to noxious heat, while DCF (2.8±0.4) and HF (2.6±0.5) did not significantly change the responses compared with control (2.2 ±0.2). The CME (35.6±0.4, 67.0±0.8) and EAF (35.2±0.4, 74.2±0.7), but not HF (55.5±0.4, 146.0±0.9) significantlyreduced duration of paw licks (seconds) in boththe neurogenic and inflammatory phases of formalin-induced paw licks compared with control (56.0±0.5, 148.0 ± 0.3), while DCF produced significant reduction in duration of paw licks in inflammatory (53.0±0.3) but not the neurogenic (55.5±0.4) pain induced by formalin when compared with the control. The CME and EAF significantly (p<0.05) delayed the onset, shortened duration of action and offered protection against picrotoxin and leptazol-induced convulsions. However, CME and its fractions did not protect strychnine-induced convulsions. The CME, EAF and DCFat 5, 10, 20mg/kg significantly reduced paw oedema size with percentage inhibitions of(25.0, 41.7, 58.3), (46.7, 46.7, 60.0) and (0.0, 9.1, 54.5) respectively compared with control. The crude methanol extract, ethyl acetate and dichloromethane fractions exhibited analgesic, anti-inflammatory and anticonvulsant activities. These support ethnomedicinal uses of the plant in the management of pain and convulsive disorders.